Pengembangan Sistem Aplikasi Penerimaan Siswa Baru di Madrasah Ibtida’iyah AL-Falahiyah Berbasis Desktop dengan Menggunakan IDE Netbeans - Muhammad Ivan Prayogi Nugroho; Aries Saifudin (Teknik Informatika Universitas Pamulang, 2022)
This development information technology makes it easy for us to get, process and present information. The information referred to is for example the collection and processing of data to provide information. One application of information technology is the development of new student admission applications in schools. With the development of this application, it can make it easier for school admins to document the data needed or used in schools. This information data can be taken from filling out forms and or voice recordings which will later be input into the computer application system that will be developed at this time. The application development method used is the Waterfall Method, which has an understanding of the earliest software development method and this method has a natural nature. This meetode has several sequences that must be completed in its entirety, the sequence is the Planning/Planning Process, Analysis, Design, Implementation and Application Testing. If it is described in more detail, the steps that must be passed are a systematic approach to get a good plan, leading to the analysis, design, conditioning, testing/verification and maintenance/maintenance stages. The steps contained in the waterfall method must be passed and completed one by one (cannot jump to the next stage if the stages have not been completed) and run sequentially. This serves to ensure that the quality of the applications obtained can produce and provide good system applications. Application development for new student admissions at this school can have a good impact on the school administration system, such as making it easier for school admins to search for detailed teacher and student biodata. at the school, the grouping of new students into several classes, setting the schedule for school subjects per grade level, to providing grade values from the results of the per-student learning scores of each subject in the school.